Integrated Coastal Zone Management Strategy for Ghana - Hewawasam, Indu (World Bank, Washington, DC, 2012)
Environmental degradation of coastal areas was identified as a key issue in Ghana's Environmental Action Plan. The central objective of the World Bank-assisted Integrated Coastal Zone Management (ICZM) initiative in Ghana, which commenced in 1995, was to identify economically, socially and environmentally appropriate interventions and projects in the coastal zone that improve the prospects for human development. ICZM is recognized by governments, international agencies and by the donor community as a process through which coastal eco-systems and resources can be protected, developed and managed in a sustainable manner. In order for implementation to be successful, effective ICZM must be based on a clear understanding of the complexities of the relation between coastal natural resources, and the coastal population that subsists on these resources. More concretely, this understanding must relate to how specific economic, political, social and technical parameters link, in a reciprocal way, specific coastal ecosystems and specific human activities.